Assessment of the control measures of the category A diseases of Animal Health Law: Rift Valley Fever. (19th January 2022) - ,; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, José Luis; Gortázar, Christian; Herskin, Mette; Michel, Virginie; et al.
Abstract: EFSA received a mandate from the European Commission to assess the effectiveness of some of the control measures against diseases included in the Category A list according to Regulation (EU) 2016/429 on transmissible animal diseases ('Animal Health Law'). This opinion belongs to a series of opinions where these control measures were assessed for several diseases, with this opinion covering the assessment of control measures for Rift Valley Fever (RVF). In this opinion, EFSA and the AHAW Panel of experts review the effectiveness of: (i) clinical and laboratory sampling procedures, (ii) monitoring period and (iii) the minimum radius of the protection and surveillance zone and the minimum length of time the measures should be applied in these zones. The general methodology used for this series of opinions has been published elsewhere; nonetheless, the transmission kernels used for the assessment of the minimum radius of the protection and surveillance zones are shown. Several scenarios for which these control measures had to be assessed were designed and agreed prior to the start of the assessment. Different risk‐based sampling procedures based on clinical visits and laboratory testing are assessed in case of outbreak suspicion, granting animal movements and for repopulation purposes. The length of monitoring period and minimum duration of measures to be implemented in the restricted zones as defined in the Delegated Regulation (30 days) are considered effective for the investigation and control of suspected and confirmed RVF outbreaks, as well as the size of protection and surveillance zone of 20 and 50 km, respectively, which are assessed as sufficient to contain disease transmission with at least 95% probability.